Issues on harmonization of human rights in Islam - Haneef, Sayed Sikandar Shah (IIUM Press, 2016)
The question of harmonization between Is1am and human rights is one of the most debatable issues in corltemporary discourse among 14or1l* academics. At the root of lhe coilroversy lies the question about the legitimacy of such an academic engagement. This is primarily because the corlmon perception is that rhe notion of human rights as embodied in Universal Declaration of Human Rights dnd its supplementary documents is bor.rnd by its underlying humanistic assumptions about humans which are anathema to the Islamic concept of human treings as bond-servants and vicegerents of God on earth- Accordingly; irs reconcilability rvith Islam in general and with Shari'ah in particular is a divisive issue among Muslim thinkers. Approaches range from vehement rejecticn to liberal treatment even to the extent of compromising fixed parts of Islamic law. A middle of the road approach within the frameworkof Islamic legal methodology of harmoaization is still in the making. It is with this agenda u: perspective that the authors of this trook have engaged on various topical issues on the subject. The central theme emerging from the papers is that the dircourse on harmonization between lslam and human rights should be pursued tluough a critical engagement wjth both intenrational human rigbts theories and Muslim intellecrual legac; within the parameterc and non-negotiable princrples of the Quian a.nd Sunnah about humans and their rights.